Diagnosis Specialist System at Palm Oil - Hassan, Norhasniza; Zakaria, Zalmiyah; Ali Shah, Zuraini; Abdullah, Noryusliza; Kasim, Shahreen (International Journal of Advanced Science Computing and Engineering, 2019)
Â The project that was developed is a computerize system that will be ableto diagnose problems happened to palm oil tree. Generally, there is twomain problem that always happened to palm oil tree; disease and pest.This system developed to store the knowledge in the related field into aknowledge base to help the newcomer in this field to make a decision tosettle the problem faced. To solve this problem, data driven searchtechnique applied to search for the symptom stored in the knowledgebase. The system developed using expert system concept. Based on thisconcept, a knowledge base was built to store all the knowledge compiled.Inference engine used to search the knowledge in the knowledge base.The knowledge based was stored in MySQL database and the inferenceengine was developed using PHP language.